Physical and Mechanical Properties of the Soil of the Bukhara Region Republic of Uzbekistan - H.R. Gaffarov; H.R. Gaffarov; Sadullaev B.B (Genius Publishing Group, 2022)
A brief description of the soils of several regions of the Republic is given.Uzbekistan and experimental data on the characteristics of soil moisture and hardness during the main processing period.
Keywords: Deep processing; irrigated soils; humus, zone